Dopexamine maintains intestinal villus blood flow during endotoxemia in rats - Schmidt, Heinfried; Secchi, Andreas; Secchi, Ruth; Bach, Alfons; Böhrer, Hubert; Martin, Eike (Critical care medicine, 1996)
Objective - To determine the influence of dopexamine, a synthetic catecholamine ligand for dopaminergic and beta2-adrenergic receptors, on alterations of the intestinal villus microcirculation in a model of normotensive endotoxemia. - Design - Randomized, controlled trial. - Setting - Experimental laboratory. - Subjects - Twenty-one male Wistar rats. - Interventions - Rats were treated with a continuous infusion of dopexamine (2.5 micro gram/kg/min; n equals 7; group A) or 0.9% saline (n equals 7; group B) during a study period of 120 mins. Both groups were given endotoxin (Escherichia coli lipopolysaccharide; 1.5 mg/kg iv) over 60 mins. Animals in the control group (n equals 7; group C) received a volume-equivalent infusion of 0.9% saline. Total volume substitution in all groups was 15 mL/kg/hr. - Measurements and Main Results - Blood flow in the intestinal villi of the distal ileum was determined using in vivo videomicroscopy at baseline, and 60 and 120 mins after the endotoxin challenge. These blood flow determinations were done by an observer who was unaware of the previous treatment of the animals. In addition, mean arterial pressure was monitored at baseline, and 15, 30, 45, 60, 75, 90, 105, and 120 mins later. - The administration of 1.5 mg/kg endotoxin alone (group B) resulted in a reduction of the intestinal villus blood flow to 74.8 plus minus 9.5% of baseline after 60 mins, and to 61.1 plus minus 8.5% of baseline after 120 mins (baseline: 7.4 plus minus 0.6 nL/min; 60 mins: 5.3 plus minus 0.8 nL/min; 120 mins: 4.4 plus minus 0.5 nL/min; p less than .05). This reduction of blood flow was associated with a decrease in the arteriolar diameters by 13.8 plus minus 2.5% after 60 mins, and by 17.1 plus minus 4.3% after 120 mins (p less than .05 vs. baseline). In contrast, villus blood flow in the dopexamine group (group A) did not show statistically significant changes during the entire study period, despite the administration of endotoxin (baseline: 8.2 plus minus 0.6 nL/min; 60 mins: 7.3 plus minus 0.8 nL/min; 120 mins: 7.8 plus minus 0.5 nL/min). No vasoconstriction of the villus arterioles was noted in this group. In control animals (group C), the blood flow (baseline: 8.1 plus minus 1.6 nL/min; 60 mins: 7.6 plus minus 1.4 nL/min; 120 mins: 7.8 plus minus 1.4 nL/min) and the arteriolar diameters remained unchanged throughout the observation period. Mean arterial pressure did not differ between groups; it remained unaltered in all groups during the entire study period. - Conclusions - Dopexamine maintains intestinal villus arterial perfusion and prevents the vasoconstriction in villus arterioles during early normotensive endotoxemia. Therefore, further studies in critically ill patients will have to determine whether the early prophylactic use of dopexamine can limit gut ischemia and prevent the development of multiple organ failure. - (Crit Care Med 1996; 24:1233-1237)